How donor selection criteria can be evaluated with limited scientific evidence: lessons learned from the TRANSPOSE project. Issue 3 (15th November 2020) - Mikkelsen, Christina; Mori, Gaia; van Walraven, Suzanna M.; Castrén, Johanna; Zahra, Sharon; MacLennan, Sheila; Seidel, Kirsten; Fontana, Stefano; Veropalumbo, Eva; Cannata, Livia; Pupella, Simonetta; Kvist, Maria; et al.
Abstract: Background and objective: Donor selection criteria (DSC) are a vital link in the chain of supply of Substances of Human Origin (SoHO) but are also subject to controversy and differences of opinion. Traditionally, DSC have been based on application of the precautionary principle. Materials and methods: From 2017 to 2020, TRANSPOSE (TRANSfusion and transplantation PrOtection and SElection of donors), a European research project, aimed to identify discrepancies between current DSC by proposing a standardized risk assessment method for all SoHO (solid organs excluded) and all levels of evidence. Results: The current DSC were assessed using a modified risk assessment method based on the Alliance of Blood Operators' Risk‐based decision‐making framework for blood safety. It was found that with limited or diverging scientific evidence, it was difficult to reach consensus and an international standardized method for decision‐making was lacking. Furthermore, participants found it hard to disregard their local guidelines when providing expert opinion, which resulted in substantial influence on the consensus‐based decision‐making process. Conclusions: While the field of donation‐safety research is expanding rapidly, there is an urgent need to formalize the decision‐making process regarding DSC. This includes the need for standardized methods to increase transparency in the international decision‐making process and to ensure that this is performed consistently. Our framework provides an easy‐to‐implement approach for standardizing risk assessments, especially in the context of limited scientific evidence.